Stratigrafi Daerah Sumalata Timur, Kabupaten Gorontalo Utara - Rivai, Alya Sri Andini; Maryati, Sri; Akase, Noviar (-, 2025)
The research area was located at coordinates 122°28’0’’- 122ᵒ36’0’ N - 0ᵒ52’0’’ - 1ᵒ2’0’ E with an area of 157 km2. Administratively, it is located in Sumalata Timur Subdistrict, North Gorontalo Regency, Gorontalo Province. The methods used in this research were surface geological surveys and laboratory analysis. Surface geological surveys included direct lithological observations at outcrops. Laboratory analysis included petrographic analysis using thin sections. The geologycal mapping aims to knowing the geological condition in East Sumalata. The lithology of the research area consists of 5 units, namely andesite unit, diorite unit, breccia unit, sandstone unit, and coastal sediment unit. The geomorphology of the research area is divided into 3 morphological units, namely the Volcanic Hills Unit, the Denudational Hills Unit, and the Marine Plains Unit.